Slow and Fast‐Release Boron Sources in Potash Fertilizers: Spatial Variability, Nutrient Dissolution and Plant Uptake. Issue 6 (11th October 2018) - da Silva, Rodrigo C.; Baird, Roslyn; Degryse, Fien; McLaughlin, Michael J.
Abstract : Core Ideas: A dual‐release boron (B) fertilizer can reduce the risks of seedling toxicity and leaching. Muriate of potash (MOP) was co‐compacted with slow‐ and fast‐release B sources. MOP+B resulted in a more uniform B spatial distribution compared to traditional bulk‐blends. Incorporation of colemanite in the formulation slowed the release of B from the MOP+B fertilizers. This novel B fertilizer may improve the synchrony between nutrient availability and crop demand. Boron (B) supply to crops is a challenging fertilization practice, due to its high mobility in soil, its narrow window between deficiency and toxicity and the necessity to evenly apply this micronutrient to the soil. We aimed to increase B fertilizer efficacy through the use of slow‐ and fast‐release borate compounds in a macronutrient carrier fertilizer. Borax, ulexite, and colemanite (alone or combined) were compacted with muriate of potash (MOP) to produce B‐enriched fertilizers varying in proportion of water‐soluble B. One such fertilizer was assessed for spatial B distribution compared with a bulk blend equivalent in a soil tray, while others were assessed for nutrient release in a soil column, and canola ( Brassica napus L.) growth in a leached and non‐leached pot trial. The compacted MOP+B fertilizer improved B distribution in soil compared to a simulated bulk blend. The release of B was fastest for borax (>93% released within 2.5 pore volumes [PV]) and slowest for colemanite (<20% released after 20 PV). The combination of slow‐ and fast‐release B sources resulted in initial fast‐release of B followed by a constant slower B release. In leached soil, the higher B losses (up to 80% of applied B) resulted in lower canola B uptake with increasing borax and decreasing colemanite in the formulation. In non‐leached soils, there was no difference in B uptake among fertilizer treatments. The use of dual release B sources in MOP+B fertilizer formulations effectively addresses the risk of B loss, and better matches crop B demands during growth.